Experimental study on the response relationship between environmental DNA concentration and biomass of Schizothorax prenanti in still water - Zhang, Jianmin; Ding, Ruiyu; Wang, Yurong; Wen, Jiating (Frontiers in Ecology and Evolution, 2022)
The superiority of the environmental DNA (eDNA) method for estimating the biomass of aquatic species has been demonstrated. However, the relationship between eDNA concentration and biomass is difficult to clarify under the influence of complex water flow and habitat conditions. It seriously restricts the popularization and application of the eDNA method in estimating aquatic biomass. In this paper, a typical fish species of rivers in southwest China, Schizothorax prenanti, was selected as the target species. Under standardized laboratory hydrostatic conditions, two environmental factors, water pH and water temperature were firstly determined through pre-experiments. Then we investigated the correlation between eDNA concentration and biomass under different body sizes and different body size compositions. The experimental results showed that water pH and the water temperature had a great influence on eDNA concentration. Therefore, the effects of these environmental factors need to be considered simultaneously when using environmental DNA concentrations to estimate biomass. Under the premise of consistent environmental conditions, the biomass of Schizothorax prenanti was positively correlated with the eDNA concentration when the individual body size was the same. For each 1% increase in biomass of the fish, the eDNA concentration of adult (larger size) fish increased by 0.98%, which was approximately equal, while the eDNA concentration of juvenile (smaller size) fish increased by 1.38%. The smaller the size of individual fish, the greater the increase of eDNA concentration with the increase of biomass, and the increase of juvenile fish was about 1.4 times that of the adult fish. When the body size composition was different but the biomass was the same, the higher the proportion of small body size individuals in the population, the higher the eDNA concentration. Special attention needs to be paid to the body size composition of the population to avoid the biomass estimation being lower than the actual value when the smaller size fish are dominant. The experimental results provide a strong basis for a more accurate estimation of aquatic biomass in reservoirs, lakes, and other still water areas by using the eDNA method.